2015
DOI: 10.1016/j.cub.2015.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Levels of Biological Activity during the Polar Night Offer New Perspectives on a Warming Arctic

Abstract: The current understanding of Arctic ecosystems is deeply rooted in the classical view of a bottom-up controlled system with strong physical forcing and seasonality in primary-production regimes. Consequently, the Arctic polar night is commonly disregarded as a time of year when biological activities are reduced to a minimum due to a reduced food supply. Here, based upon a multidisciplinary ecosystem-scale study from the polar night at 79°N, we present an entirely different view. Instead of an ecosystem that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
113
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(127 citation statements)
references
References 57 publications
14
113
0
Order By: Relevance
“…It has been shown that large numbers of CIV and CV copepodids of both C. finmarchicus and C. glacialis were already present in surface waters in our study (Fig. 5a-b), which is similar to the midwinter observations of Berge et al (2015) from the same region. Two recent seasonal studies by Lischka and Hagen (2016) and Bandara et al (2016) have also described seasonal vertical patterns in abundance of Calanus age structure sampled by a modified Apstein closing net (100 μm mesh size, 0.2 m 2 mouth opening) and a larger WP3 net (mesh size of 1000 μm, 1 m 2 area of the opening) in Kongsfjorden and Billefjorden, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…It has been shown that large numbers of CIV and CV copepodids of both C. finmarchicus and C. glacialis were already present in surface waters in our study (Fig. 5a-b), which is similar to the midwinter observations of Berge et al (2015) from the same region. Two recent seasonal studies by Lischka and Hagen (2016) and Bandara et al (2016) have also described seasonal vertical patterns in abundance of Calanus age structure sampled by a modified Apstein closing net (100 μm mesh size, 0.2 m 2 mouth opening) and a larger WP3 net (mesh size of 1000 μm, 1 m 2 area of the opening) in Kongsfjorden and Billefjorden, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…perminuta did not start to degrade its chloroplasts for energy mobilization. Also Berge et al (2015a) confirmed in natural phytoplankton communities from Svalbard at the end of the polar night a missing lag-phase with respect to initiation of photosynthesis upon re-illumination, which indicates that chloroplast were not degraded during the dark season. In which way temperature affects the heterotrophic uptake potential or the potential degradation rate of chloroplasts under dark conditions in polar diatoms is not known.…”
Section: The Lipids Metabolism Under Darknessmentioning
confidence: 65%
“…Recently, Berge et al (2015) reported similar levels of macrobenthic abundance and sediment community respiration rates in deep Kongsfjorden basins in January and other seasons that were characterized by higher supply of organic matter produced in the water column. These observations in the deeper (90-300 m) basins of the fjord agree with the previous report of Kędra et al (2012) who compared Kędra et al (2012) found no significant difference in abundance or biomass, and only slightly lower species richness in the winter season that they attributed to increased disturbance in shallow water produced by ice and storms.…”
Section: Discussion Seasonal Variability In Benthic Communitiesmentioning
confidence: 89%
“…Marine biological productivity in the Arctic is highly constrained by the light availability (determined by solar angle) and ice presence and thickness, which undergo marked seasonal cycles (Wassmann and Reigstad 2011;Berge et al 2015). In the open ocean, organic matter is produced by phytoplankton and ice algae.…”
Section: Introductionmentioning
confidence: 99%